Relationship between degree of heparin anticoagulation and clinical outcome in patients receiving potent P2Y12-inhibitors with no planned GPI during primary percutaneous coronary intervention in acute myocardial infarction: a VALIDATE-SWEDEHEART substudy - Sharma, Tania; Rylance, Rebecca; Karlsson, Sofia; Koul, Sasha; Venetsanos, Dimitrios; Omerovic, Elmir; Fröbert, Ole; Persson, Jonas; James, Stefan; Erlinge, David (European heart journal. Cardiovascular pharmacotherapy, 2020)
Aims: Heparin is the preferred choice of anticoagulant in percutaneous coronary intervention (PCI) for acute myocardial infarction (MI). An established dosage of heparin has not yet been determined, but treatment may be optimized through monitoring of activating clotting time (ACT). The aim of this study was to determine the relationship between heparin dose or ACT with a composite outcome of death, MI or bleeding using data from the registry-based, randomized, controlled and open-label VALIDATE-SWEDEHEART-trial, although patients were not randomized to heparin dose in this sub-study. Methods and results: Patients with MI undergoing PCI and receiving treatment with a potent P2Y12-inhibitor and anticoagulation with heparin, without the planned use of glycoprotein IIb/IIIa inhibitor (GPI), were enrolled in this substudy. The primary endpoint was a composite end point of death, MI and bleeding at 30 days. The individual components and stent thrombosis were analyzed separately. We divided patients into groups according to the initial dose of unfractionated heparin during PCI (<70U/kg, 70-100U/kg and >100U/kg) or ACT (ACT <250 sec, 250-350 sec and >350 sec) as well as investigating them as continuous variables in Cox proportional hazards models using univariable and multivariable analyses . No major differences were noted between heparin stratified in groups (p = 0.22) or heparin as a continuous variable in relation to the primary composite endpoint HR 1.0 CI (0.99-1.01) for heparin dose/kg. No differences were found between ACT stratified in groups (p = 0.453) or ACT in seconds HR 1.0 CI (0.99-1.00) regarding the primary endpoint. The individual components of death, MI, major bleeding and stent thrombosis were not significantly different across heparin doses or ACT levels either. Conclusion: We found no association between heparin dose or ACT levels and death, MI bleeding complications or stent thrombosis. Therefore, there is no strong support for a specific heparin dose or mandatory ACT monitoring in patients treated with potent P2Y12-inhibitors with no planned GPI.